Religious indoctrination of youth in Malaysia - Maisarah Ahmad Razman; Nurul Nadia Brahanuddin; Filzah Hannani Zainudin Azman (Penerbit Universiti Kebangsaan Malaysia, 2023)
This article seeks to highlight on the issue in determining a youth’s religious freedom and practice the religion that interests them. Article 11(1) of Federal Constitution of Malaysia provides for the fundamental right of a person to profess and practise his or her religion subject to certain restrictions. Nonetheless, Article 12(4) of Federal Constitution restricted the religious freedom of a person under the age of 18 whereby it shall be decided by his or her parent or guardian. Article 11(1) of the Federal Constitution is a fundamental right but with the exemption in Article 12(4), it invites the question whether a youth has a right to religious freedom. It examines several controversial cases which tackle the essential question of whether the Malaysian conception and practice of youth’s religious freedom is consistent with constitutional rights in Article 11(1). This study utilized legal doctrinal research in the context of the Federal Constitution, legal issues and its application, including the implementation of the right to religious freedom for youth in another country. This paper demonstrates that while religious freedom is constitutionally guaranteed in Malaysia, but youth under the age of 18 have no rights to decide for themselves the religion they want to practice. Thus, this paper proposes that Article 12(4) should be amended in order to stop the discrimination against youth under the age of 18 in their right to freedom of religion and some other suggestions.